Kemampuan mobilitas dan derajat luka tekan pasien rawat inap - Muskhab Eko Riyadi; Ahmad Ikhwan Hanafi; Ni Ketut Arningsih (Health Sciences and Pharmacy Journal, 2020)
The occurrence of pressure ulcer is directly related to the duration of immobility. If the suppression continues for a long time, small vascular thrombosis and tissue necrosis will occur. In bone protrusions that hold weight are more susceptible to pressure sores and are often found in people with limited movement because they are unable to change positions to remove pressure. Objective is to determine the relationship of mobility ability with the degree of pressure ulcer on inpatients at Wonosari Hospital in Gunungkidul Regency. This research was non-experimental research with cross-sectional design. The samples in this study were patients treated in the surgical, internal and neurological ward of Wonosari Hospital in Gunungkidul Regency. The sampling technique used the simple random sampling technique. While the statistical test used the Pearson test. Results showed that the average scale of mobility ability of inpatients was 3 scale (mean 2,70), while the average value of the degree of pressure ulcer in the inpatient ward of Wonosari Hospital was degree I (mean 1,32). Conclusion of this research was there was a significant correlation between mobility ability and the degree of pressure ulcer of the patient in the inpatient room at Wonosari Hospital in Gunungkidul Regency with a significance value of 0.000 (ρ < 0,05).